A graphical user interface (GUI) for the air pollutant index (API) in Klang Valley / Wan Ahmad Khusairi Wan Chek - Wan Chek, Wan Ahmad Khusairi (2007)
Pollutant may come from air, river, sea, land and etc. In this project the analysis will be focusing on the air pollution. To reflect the dangerous of the air pollution effect on human health the Air Pollutant Index (API) is introduced. Air Pollution Index (API) is a system that provides information about the level of the air quality level in simple terms to the public. There a five major pollutants parameter included in Malaysia's API which consist of ozone (03), nitrogen dioxide (N02), carbon dioxide (CO), sulphur dioxide (S02) and suspended particulate matter less than 10 micron(PM10). The main target of developing the Graphical User Interface or GUis is to create an interface that take advantages of computer graphic capabilities to transformed the statistical Air Pollution Index (API) data into graphical form which make it easier to be analyzed. In this final project the GUI for determining the API has being developed and tested.